CTNI-37. EFFICACY OF ONC201 IN PATIENTS WITH ONC201 FOR RECURRENT H3 K27M-MUTANT DIFFUSE MIDLINE GLIOMA. (9th November 2020) - Arrillaga-Romany, Isabel; Kurz, Sylvia; Tarapore, Rohinton S; Sumrall, Ashley; Butowski, Nicholas; Harrison, Rebecca; de Groot, John; Chi, Andrew; Shonka, Nicole; Umemura, Yoshie; Odia, Yazmin; Mehta, Minesh; et al.
Abstract: H3 K27M-mutant diffuse midline gliomas (DMG) have a dismal prognosis. We report an integrated analysis for ONC201, a DRD2 antagonist and ClpP agonist, in patients with recurrent H3 K27M DMG administered as monotherapy in 3 clinical studies (NCT03295396, n=20; NCT02525692, n=6; or expanded access, n=4) by independent, central radiology review among 30 patients. At baseline, patients had measurable contrast-enhancing disease by RANO criteria, KPS > 60, and were >90 days from prior radiation. Patients with primary lesions that involved the pons or spinal cord or had evidence of leptomeningeal or cerebrospinal fluid dissemination were excluded. ONC201 was orally administered at 625 mg (scaled by body weight for patients < 18 years old) weekly in 29 patients and every 3 weeks in 1 patient. Median age was 31 years (range 8–70; two patients < 18). There were 16 women and 14 men. Tumors were predominantly thalamic (73%), with other locations including the cerebellum (5%), brainstem (non-pontine) (3%), basal ganglia (3%), and midbrain (3%). Median time from prior radiation was 7.5 months. The most frequent drug-related adverse events were low grade nausea (10%) and fatigue (10%). Nine patients (30%) had >50% regression of T1 contrast enhancement and 11 (36.7%) patients had regression of T2/FLAIR. Objective response rate and progression-free survival by RANO criteria, as well overall survival will be reported. Among 8 patients with sustained radiographic regressions, 6 were tapered off dexamethasone and 4 had improvement in KPS. Five patients (16.7%) remain on treatment with a median of 9.5 months (range 7.3–12). In conclusion, single agent ONC201 is well tolerated and clinically active in recurrent H3 K27M DMG patients.